"Where do you want us to go …, so that you may eat?": Performing the Lord’s Supper in Cemeteries and Cities - Standhartinger, Angela (New Testament studies, 2025)
Based on recent theoretical reflections on the links between space and rituals, this paper re-examines early Christian meal practice. Since the 1980s, many scholars have agreed that early Christ groups met in private houses inside a given city and celebrated their meals in the form of the Greco-Roman banquet. However, the idea that early Christ groups met ‘almost exclusively’ in private houses has been disputed in recent years. This paper expands on one of the suggested alternative meeting spaces: the graveyard. Tombs of the rich and poor lined the roads running in and out of an ancient city. The tradition handed down by Paul and the Synoptic Gospels (1 Cor 11.23-5/Mark 14.22-4 par.) can be located here. It contains a story fragment linked in form and content to laments that might have been part of a dramatically narrated passion account with a subsequent mortuary meal. This shows how spatial contextualisation can expand the reconstruction of the diversity of early Christian meal celebrations.